2004
DOI: 10.1291/hypres.27.821
|View full text |Cite
|
Sign up to set email alerts
|

The Thiazide-Sensitive Na+-Cl- Cotransporter Gene, C1784T, and Adrenergic Receptor-β3 Gene, T727C, May Be Gene Polymorphisms Susceptible to the Antihypertensive Effect of Thiazide Diuretics

Abstract: IntroductionThiazide diuretics (TZDs) have been most widely used as a first line antihypertensive drug (1,2). Recently, the ALLHAT study confirmed the usefulness of TZDs for the reduction of blood pressure (BP) and cardiovascular diseases in comparison with newer antihypertensive drugs, including Ca channel blockers (CCBs) such as amlodipine and angiotensin converting enzyme inhibitors (ACEIs) such as lisinopril in about 40,000 hypertensive patients with high risk factors (3). TZDs are not only effective as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 41 publications
1
31
1
Order By: Relevance
“…Rs4994, a polymorphism in ADRB3, has been evaluated in hypertensive studies. This variant is associated with essential hypertension in Han Chinese 64 , mean thiazide BP response in Japanese individuals 65 , and pulse pressure variation between atenolol and losartan in whites 17 . These associations were not corrected for a multiple testing penalty and have not been replicated.…”
Section: Candidate Pharmacodynamic Polymorphisms Of Adrenergic Responsementioning
confidence: 99%
“…Rs4994, a polymorphism in ADRB3, has been evaluated in hypertensive studies. This variant is associated with essential hypertension in Han Chinese 64 , mean thiazide BP response in Japanese individuals 65 , and pulse pressure variation between atenolol and losartan in whites 17 . These associations were not corrected for a multiple testing penalty and have not been replicated.…”
Section: Candidate Pharmacodynamic Polymorphisms Of Adrenergic Responsementioning
confidence: 99%
“…Therefore, with an increase of TSC activity, greater amounts of sodium and chloride might be transported from the kidneys to the plasma, resulting in an increased efficiency of kidney sodium reabsorption. Matayoshi et al (2004) indicated that the BP in patients with essential hypertension who were homozygous for the major alleles of the SLC12A3 C1784T mutation was reduced by thiazide diuretics; however, the BP levels in those patients homozygous for the minor allele or in heterozygotes were not changed by thiazide diuretics. Thus, they suggested that Japanese patients with essential hypertension carrying the C1784T mutation of SLC12A3 were susceptible to the antihypertensive effect of thiazide diuretics.…”
Section: Introductionmentioning
confidence: 99%
“…These studies investigated the association of RAS gene polymorphisms and responses to antihypertensive drugs, including angiotensin I-converting enzyme inhibitors (ACEIs), 13 angiotensin II receptor blockers (ARBs), 14 beta blockers 15 and diuretics. 16 Our group also endeavored to clarify the susceptible gene polymorphisms to thiazide diuretics 17 and calcium channel blockers (CCBs) 18 by candidate genes approaches, although there are very limited reports about gene polymorphisms associated with the effects of CCBs. We clarified the associations between CACNA1D rs312481G4A and rs3774426C4T, and CACNA1C 527974G4A and treatment with a more significant reduction in BP for the combined presence of the L type of CCB's antihypertensive effect in this paper.…”
Section: Current Trends In Pharmacogenetic/ Pharmacogenomic Studies Omentioning
confidence: 99%